Спосіб побудови дотичних у вузлах спиралеподібних дискретно представлених кривих із використанням спеціальної функції - Щербина, Віктор Михайлович; Щербина, Виктор Михайлович; Shcherbyna, Viktor; Мацулевич, Олександр Євгенович; Мацулевич, Александр Евгеньевич; Matsulevych, Oleksandr; Коломієць, Сергій Матвійович; Коломиец, Сергей Матвеевич; Kolomiiets, Serhii (My University, 2019)
UK: У роботі досліджується дискретна інтерполяція неоднозначних дискретно представлених кривих (ДПК) довільної конфігурації в локальній системі координат та глобальне формування вузлових дотичних на основі застосування, для проектування, спеціальної функції, які гарантують відсутність осциляції всього обводу. Дослідження полягає в виявлені можливості використання неперервного геометричного моделювання на основі спеціальної функції і призначення дотичних у вузлах вихідної ДПК при локальних методах згущення та глобальне призначення дотичних при методах згущення спіралеподібних та замкнених кривих ліній на основі спеціальної функції. Представлений у роботі спосіб згущення дискретно представлених кривих (ДПК), дозволяє, окрім методів глобальної інтерполяції зазначених кривих, використовувати методику локальної неперервної інтерполяції. RU: В работе предлагается применение весовых коэффициентов при аппроксимации дискретно представленных кривых методом дискретного метода наименьших квадратов (ДМНК), что позволяет приблизить решение до заданного узла или отдалить от него. Предложенная геометрическая схема позволяет назначать согласованные характеристики в узлах ДПК. Параметрами формообразования являются весовые коэффициенты, задающие положения точек сгущения. Схема позволяет назначать в исходных точках касательные прямые и формировать одномерные обводы с учётом этих характеристик. EN: At designing the productions causing use of modern methods of construction of form-building surfaces of the complex geometrical form, there is a necessity for development of alternative methods and algorithms of their reception. At computer realization of tasks of construction of complex surfaces it is extremely necessary to have adequate algorithms of construction of flat contours of sections of projected surfaces. Discrete computer modeling of surfaces complex geometrical provides forms of applications of original methods of reception of flat contours of surfaces which are projected. One of such methods is the method approximation discretely submitted curves by concrete criterion. In work application of weight factors is offered at approximation of discretely submitted curves by a method of a discrete method of the least squares (DMLS) that allows to approach the decision up to the set unit or remove from him. The resulting algorithm allows to form the WPC on the basis of any point series. At the same time, there is the possibility of step-by-step control and correction of the resulting solution, the imposition of additional conditions on it, the absence of oscillations is guaranteed. The proposed geometric scheme allows you to assign consistent characteristics in the nodes of the WPC. Forming parameters are weighting factors that define the positions of the condensation points. The scheme allows assigning tangent lines at the source points and forming one-dimensional contours taking these characteristics into account. The formation of flat one-dimensional contours with the provision of control of differential-geometric characteristics makes it possible to simulate surfaces of complex shape according to specified conditions.
Аппроксимация дискретно представленой кривой с использованием дискретного метода наименьших квадратов с весовыми коэффициентами
Approximation with weight factors by criterion of a discrete method of the least squares (dmls)
Keywords: геометричне моделювання; дискретна інтерполяція; спіралеподібна дискретно представлена крива (ДПК); супроводжуюча ламана лінія (СЛЛ); дотична; спеціальна функція